2014
DOI: 10.2151/sola.2014-044
|View full text |Cite
|
Sign up to set email alerts
|

Data Assimilation with Error-Correlated and Non-Orthogonal Observations: Experiments with the Lorenz-96 Model

Abstract: This study aims to investigate the impact of observation error correlations and non-orthogonal observation operators on analysis accuracy using a chaotic dynamical model known as the Lorenz-96 40-variable model, extending the previous study by Miyoshi et al. using a simple two-dimensional conceptual model. The results corroborate Miyoshi et al.'s conceptual study and show that the analysis is more accurate when the row vectors of a linear observation operator are correlated positively (negatively) with negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Furthermore, when the assumed statistics used in the assimilation are not exact, with careful interpretation of the results, the diagnostic can still provide useful information about the true observation uncertainties (Waller et al 2016b;Ménard 2016). The diagnostic has further limitations; these include the assumption that the observation operator is linear (Terasaki and Miyoshi 2014) and the fact that ergodic, isotropic and homogeneous assumptions are often made in order to obtain sufficient sample residuals (Todling 2015). Because of the limitations of the diagnostic, observation error statistics estimated using this methodology should be interpreted as indicative, rather than necessarily quantitatively perfect.…”
Section: Limitations Of the Diagnosticmentioning
confidence: 99%
“…Furthermore, when the assumed statistics used in the assimilation are not exact, with careful interpretation of the results, the diagnostic can still provide useful information about the true observation uncertainties (Waller et al 2016b;Ménard 2016). The diagnostic has further limitations; these include the assumption that the observation operator is linear (Terasaki and Miyoshi 2014) and the fact that ergodic, isotropic and homogeneous assumptions are often made in order to obtain sufficient sample residuals (Todling 2015). Because of the limitations of the diagnostic, observation error statistics estimated using this methodology should be interpreted as indicative, rather than necessarily quantitatively perfect.…”
Section: Limitations Of the Diagnosticmentioning
confidence: 99%
“…The effect of H on the correlations explains the results given by Miyoshi et al () and Terasaki and Miyoshi (), which showed that when a and χ r are different signs the observations have the greatest information (see e.g. Figure (f)).…”
Section: Two‐variable Problemmentioning
confidence: 99%
“…This is similar to the common treatment in NWP systems for, e.g., Atmospheric Motion Vectors which are known to have considerable horizontal error correlations. Miyoshi et al [2013] and Terasaki and Miyoshi [2014] reported potential improvements by considering the observation error correlations explicitly in data assimilation. Including the horizontal error correlation in the NICAM-LETKF system is planned in future applications.…”
Section: 1002/2016jd025355mentioning
confidence: 99%